Formação inicial de professores para a educação especial inclusiva: um olhar para as licenciaturas da UFES - Leite, Lucas de Souza (2022)
The last decades represents a historical period where inclusive perspective has been consolidated in the global scenario, emerging as guideline to people’s with disabilities schooling process at the common schools. In this context, emphasize the initial teacher education becomes an imperative to the inclusion processes. Considering this and making the teacher training program of the Federal University of Espírito Santo (UFES) as empirical field, the present research aimed to analyze the contribution of initial teacher education in the construction of knowledge related to inclusive special education and, consequently, to students’ with disabilities school inclusion at the common schools. For that, this research analyzed how inclusive special education thematic area is outlined in the legal frameworks that orientate teacher training in Brazil; the curriculum propositions of teacher training courses – current curriculum (2018) – focusing knowledge conception, related to inclusive special education, underlying to offers conditions and curriculum organization; and also, teachers and students conception about inclusive special education, about the initial teacher education and the students with disabilities inclusion at the common education. The qualitative research is configured as a case study and uses document analysis, interview with the university lecturer from and questionnaires with the students of graduation courses as techniques of data production. The analyses are based on the theoretical and epistemological constructs of Norbert Elias' Figurational Theory (1990; 1994a; 1994b; 2000; 2006) and has the meanings given to teaching based on Nóvoa (1992) e Tardif (2008). We analyzed 17 teacher training courses (their Pedagogical-Curricular Projects [PPC]) the course menus and the Teaching Plans), as well as interviewed three professors and obtained 93 responses from the questionnaires. The results lead us to the understanding that the period of initial teacher education is configured as a period with great pedagogical potential for the mobilization of knowledge related to inclusive special education. Furthermore, the research showed us that the training context, understood by the attitudes of the teacher educators and the architectural facilities, has a strong influence on the development and assumption of social attitudes more inclined towards school inclusion by teacher training students, showing the indissociability and interdependence between the different factors that constitute the chain of relationships established during the period of teacher training. The results of the study lead us to the understanding that in this process of initial formation, although the presence of subjects in the curriculum is not an absolute guarantee of mobilization of knowledge, these subjects - which need to seek a common point between theoretical teaching and know-how - are extremely important for this purpose.